Pure Rickart Modules - Sabti, Hassan; Hamad, Bahar (Iraqi Journal of Science, 2024)
This paper focuses on the study of pure Rickart modules (or PR-modules for short), which are a class of modules over a commutative ring with identity. The main objective is to investigate the properties and characterizations of these modules, as well as their relationship with other classes of modules such as free, projective, and flat modules. This paper also explores the connections between PR-modules and various algebraic structures such as rings. The results obtained in this study provide a deeper understanding of the structure and behavior of PR-modules, which can have important applications in algebraic geometry, representation theory, and other areas of mathematics. Some results about PR-module have been investigated in this paper, for example we demonstrate a module  is PR-module if and only if for every , is pure submodule of  (or  for short). Also, some kind of generalization of these rings have been constructed and demonstrated in term of PR-modules.